Collagen co-localized with macrovesicular steatosis better differentiates fibrosis progression in non-alcoholic fatty liver disease mouse models - Wang, Xiao-Xiao; Jin, Rui; Li, Xiao-He; Yang, Qiang; Teng, Xiao; Liu, Fang-Fang; Wu, Nan; Rao, Hui-Ying; Liu, Feng (Frontiers in Medicine, 2023)
Background: Non-alcoholic fatty liver disease (NAFLD) is a global commonly occurring liver disease. However, its exact pathogenesis is not fully understood. The purpose of this study was to quantitatively evaluate the progression of steatosis and fibrosis by examining their distribution, morphology, and co-localization in NAFLD animal models. Methods: Six mouse NAFLD groups were established: 1) western diet (WD) group; 2) WD with fructose in drinking water (WDF) group; 3) WDF + carbon tetrachloride (CCl4) group, WDF plus intraperitoneal injection of CCl4; 4) high-fat diet (HFD) group, 5) HFD with fructose (HFDF) group; and 6) HFDF + CCl4 group, HFDF plus intraperitoneal injection of CCl4. Liver tissue specimens from NAFLD model mice were collected at different time points. All the tissues were serially sectioned for histological staining and second-harmonic generation (SHG)/two-photon excitation fluorescence imaging (TPEF) imaging. The progression of steatosis and fibrosis was analyzed using SHG/TPEF quantitative parameters with respect to the non-alcoholic steatohepatitis Clinical Research Network scoring system. Results: qSteatosis showed a good correlation with steatosis grade (R: 0.823–0.953, P<0.05) and demonstrated high performance (area under the curve [AUC]: 0.617–1) in six mouse models. Based on their high correlation with histological scoring, qFibrosis containing four shared parameters (#LongStrPS, #ThinStrPS, #ThinStrPSAgg, and #LongStrPSDis) were selected to create a linear model that could accurately identify differences among fibrosis stages (AUC: 0.725–1). qFibrosis co-localized with macrosteatosis generally correlated better with histological scoring and had a higher AUC in six animal models (AUC: 0.846–1). Conclusions: Quantitative assessment using SHG/TPEF technology can be used to monitor different types of steatosis and fibrosis progression in NAFLD models. The collagen co-localized with macrosteatosis could better differentiate fibrosis progression and might aid in developing a more reliable and translatable fibrosis evaluation tool for animal models of NAFLD.